Ectopic pregnancy in a non-communicating rudimentary uterine horn: a ticking bomb in a closed room - Sharma, Vinutha M.; Babu, Divya; T., Govinda Raju B.; Babu, Sandhya (International Journal of Research in Medical Sciences, 2025)
Unicornuate uterus with rudimentary horn is a rare Müllerian anomaly occurring in 2.5-13% of cases, resulting from incomplete midline unification of Müllerian ducts during organogenesis. Pregnancy in a non-communicating rudimentary horn occurs in approximately 1 in 76,000-150,000 pregnancies and poses significant risks, including uterine rupture and severe haemorrhage. A 26-year-old woman presented at 8 weeks of gestation with her first pregnancy. Ultrasound revealed a right non-communicating horn pregnancy of 7 weeks with a gestational sac diameter of 24.9 mm and absent cardiac activity. β-hCG was 1,35,066 IU/l. MRI confirmed a unicornuate uterus with a non-communicating uterine horn pregnancy showing yolk sac presence and fetal pole absence. The patient was treated with systemic methotrexate 70 IU. Following an inadequate initial response (β-hCG: 89,344 IU/l after 7 days), a second dose was administered. Subsequently, β-hCG showed a declining trend: 1400, 457, 268.25, and 54 IU/l over consecutive weeks, confirming successful treatment. The patient later conceived naturally, achieving left horn intrauterine pregnancy and is currently at 24 weeks gestation with normal antenatal progress including normal nuchal translucency and anomaly scan. Early diagnosis and management of ectopic pregnancy in non-communicating uterine horns prevents fatal maternal complications. High clinical and radiological suspicion is essential for timely diagnosis. Systemic methotrexate represents an effective conservative treatment option, allowing preservation of fertility and subsequent successful pregnancy outcomes in the functional uterine horn.